A natural hybrid of Impatiens, in the introduced range, demonstrated by sequence analysis of the nuclear ribosomal DNA-gene repeat. Issue 2 (3rd April 2019) - van Valkenburg, J.L.C.H.; Schoenenberger, N.; van de Vossenberg, B.T.L.H.; Man in 't Veld, W.A.; Westenberg, M.; Boer, E.
ABSTRACT: In a nature reserve, in Ticino canton in Switzerland amidst a mixed population of non-native Impatiens parviflora and I. glandulifera aberrant plants of I. parviflora were observed. A herbarium voucher and seeds were collected and seedlings subsequently raised in a greenhouse. Molecular analysis for ITS region and chloroplast markers revealed the plants to be a hybrid between I. parviflora and I. balfourii, another non-native Impatiens species occurring in the Ticino canton. No crossing out nor reduced fertility was observed in F2 and F3 generations, raised in a greenhouse. Sizeable populations of the hybrid have been observed in 2014 in the Ticino canton in the absence of the parental species. Nuclear genome size as measured by flow cytometry with propidium iodide did not indicate polyploidy and the ITS region remained 100% uniform. Therefore a homoploid hybrid speciation event is assumed.